2017
DOI: 10.1097/sla.0000000000002397
|View full text |Cite
|
Sign up to set email alerts
|

Liver Function in Patients With Nonalcoholic Fatty Liver Disease Randomized to Roux-en-Y Gastric Bypass Versus Sleeve Gastrectomy

Abstract: Patients with NASH undergoing RYGB are more susceptible to early transient deterioration of liver function than after SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 28 publications
4
56
0
1
Order By: Relevance
“…Weight loss after LSG resulted in a significant reduction of ALT, AST, GGT, and ALT/AST ratio, and we proved that the improvement of transaminases is related to the degree of weight loss. This fact has already been described in other recent studies [23-26]. In the Swedish Obese Subjects Study [46] the reduction in ALT levels was proportional to the degree of weight loss.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Weight loss after LSG resulted in a significant reduction of ALT, AST, GGT, and ALT/AST ratio, and we proved that the improvement of transaminases is related to the degree of weight loss. This fact has already been described in other recent studies [23-26]. In the Swedish Obese Subjects Study [46] the reduction in ALT levels was proportional to the degree of weight loss.…”
Section: Discussionsupporting
confidence: 77%
“…No robust data on the effects of LSG on liver fat are actually available and the exact mechanisms that lead to the improvement in NAFLD following bariatric surgery are not completely understood [23, 24, 26, 27]. Our study proved that LSG have a significant positive effect on biochemical parameters of NAFLD with a correlation between the improvement of ALT/AST ratio and the decrease of BMI and TG.…”
Section: Discussionsupporting
confidence: 50%
“…The study was approved by the Ethical Committee at the Medical University of Warsaw, and all patients gave informed consent for echocardiography and abdominal ultrasound examination. Each patient underwent a wedge liver biopsy during the bariatric surgery as a part of the routine protocol implemented at the Department of General, Transplant and Liver Surgery, Medical University of Warsaw, Poland [ 23 ]. Tissue sample was extracted from the subcapsular part of the left liver lobe.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported that in obese patients with T2DM, SG normalizes liver function tests after 12 months, whereas RYGB was not able to achieve normal transaminases (129). These findings are supported by a recent RCT, which also found that SG normalizes liver function tests within 12 months after surgery but not RYGB (130). In contrast to these findings, a very recent analysis from our cohort of all bariatric patients found that the liver stiffness may be better improved by RYGB than SG (131).…”
Section: Nafld/nash Improvement After Metabolic Surgerymentioning
confidence: 55%